Understanding Support for Populist Radical Right Parties: Toward a Model That Captures Both Demand-and Supply-Side Factors - Mols, Frank; Jetten, Jolanda (Frontiers in Communication, 2020)
Populist radical-right parties (PRRPs) were once considered ‘fringe parties’ condemned to permanent opposition. Their electoral success, so it was argued, would be short-lived, especially once in office, when the party would face complex policy challenges and become accused of overpromising. However, PRRPs have now joined coalition governments in many countries, without suffering voter losses. This raises the question of how PRRPs managed to break through this ‘glass ceiling’. In this conceptual paper we review research seeking to identify a ‘winning formula’. We argue that in order to make progress we need to avoid unhelpful ‘either-or’ thinking, and capture the interplay between demand-side factors (reasons why voters become attracted to PRRPs) and supply-side factors (the things PRRPs do to increase their electoral appeal). More specifically, we propose a new integrative analytical framework, one that enables us to study the way in which supply- and demand-side factors interact and reinforce each other. We conclude this paper by emphasising the importance of accounting for the interaction between supply and demand. It is only in this way that we can enhance our capacity to account for the powerful ways in which PRRP leaders persuade voters that they alone can solve society’s most pressing problems.